The sea in winter - Day, Christine, 1993- (Heartdrum, an imprint of HarperCollinsPublishers, 2021)
After an injury sidelines her dreams of becoming a ballet star, Maisie is not excited for her blended family's midwinter road trip along the coast, near the Makah community where her mother grew up.